Isotherm adsorption characteristics of carbon microparticles prepared from pineapple peel waste - Nandiyanto, Asep Bayu Dani; Santiuly Girsang, Gabriela Chelvina; Maryanti, Rina; Ragadhita, Risti; Anggraeni, Sri; Fauzi, Fajar Miraz; Sakinah, Putri; Astuti, Asita Puji; Usdiyana, Dian; Fiandini, Meli; Dewi, Mauseni Wantika; Al-Obaidi, Abdulkareem Sh. Mahdi (Communications in Science and Technology, 2020)
The objective of this study was to investigate isotherm adsorption of carbon microparticles from pineapple peel waste. Carbon microparticles were prepared by carbonizing pineapple peel waste at 215-250°C and grinding using a saw-milling process. To investigate adsorption properties of carbon microparticles, experiments were done by evaluating adsorption of curcumin (as a model of adsorbate) in the ambient temperature and pressure under constant pH condition. To confirm the adsorption characteristics, carbon particles with different sizes (i.e., 100, 125, and 200 ?m) were tested, and the adsorption results were compared with several standard isotherm adsorption models: Langmuir, Freundlich, Temkin, and Dubinin- Radushkevich. To support the adsorption analysis, several characterizations (i.e., optical microscope, sieve test, and Fourier transform infrared analysis) were conducted. The adsorption test showed that the adsorption profile is fit to the Freundlich model for all variations, indicating the multilayer adsorption process on heterogeneous surfaces and interactions between adsorbate molecules. The results from other isotherm models also confirmed that the adsorption process occurs physically via Van der Waals force in binding adsorbate on the surface of adsorbent.